Permeability And Durability Of Semi-Flexible Pavement With Waste Tire Rubber And Natural Zeolite Addition - Hamzami; Munirwansyah; Muttaqin Hasan; Sugiarto (Faculty of Engineering, Malikussaleh University, 2018)
The durability of pavement is caused by the problem of surface drainage in every part of the highway, which may be different and requires consideration after special care depending on the location conditions. Good drainage is generally achieved by providing material gradations that are in accordance with adequate permeability with structural adequacy that depends on site conditions by taking into account the intensity of rain in the area. The purpose of this study was to study the permeability of falling head permeability (FHP) methods and the durability of the Marshall method from semi-flexible hardness using used tire rubber and natural zeolite as a substitute for asphalt and cement. The mix design of porous asphalt is started with determination of optimum asphalt proportion with open graded aggregat as spesified in Australian Asphalt Pavement Assosiation (AAPA) 2004.. The asphalt was then replaced with 3%, 4% and 5% waste tire rubber and the Marshall Test was conducted. The cement mortar with 0 %, 5 %, 10 %, 15 % and 20 % natural ziolite was injected to porous asplalt specimens. Permeability tests and durability are conditioned according to ASTM C67091a at 14 days of specimen age. The test results showed that the highest permeability value was obtained at 0.0529 cm / second and the highest durability was 91.45% in 15% of Aceh's natural zeolites. The value of durability is much higher than the required specifications of 75%.